Exact solutions for some of the fractional integro-di?erential equations with the nonlocal boundary conditions by using the modi?cation of He’s variational iteration method - Irandoust-pakchin, Safar; Abdi-mazraeh, Somayeh (International Journal of Advanced Mathematical Sciences, 2013)
In this paper, the modification of He's variational iteration method (MVIM) is developed to solve fractional integro-differential equations with nonlocal boundary conditions. It is shown that by choosing suitable initial approximation, the exact solution obtains by one iteration. It is illustrated that the propose method is effective and has high convergency rate.